Determination of The Effects of Different Silvicultural Treatments on Soil Respiration, Temperature and Moisture Properties in The Skidding Trail Depending on Topographic Factors - Ozer Genc, Cigdem; Karayiğit, Hasan Kürşat (Kastamonu University, 2025)
Aim of study: This study investigates how silvicultural treatments and skid trails influence soil respiration in relation to soil moisture, temperature, and topographic factors within forest ecosystems. Area of study: This study was carried out depending on topographical factors (slope, aspect, elevations) as a result of silvicultural treatments in Pinus Nigra stands in Kastamonu Forestry Regional Directorate Daday Business Directorate. Material and method: Soil respiration, temperature and moisture measurements were made at different slope, elevation and aspect groups from the control points and skidding trail for regeneration and tending treatments. Main results: Silvicultural treatments did not significantly affect soil respiration or moisture on skid trails, while soil temperature was influential in both treatments. Elevation was the most important topographic factor, affecting all soil properties. Slope influenced only soil moisture, whereas aspect affected respiration and moisture but not temperature. Highlights: The study provides insights into how skid trails from different silvicultural treatments impact soil properties and underlines the importance of ecologically based approaches for sustainable forest management.